Abundance variation of Porichthys margaritatus (Pisces: Batrachoididae) throughout thermic and bathymetric gradients in the central Mexican Pacific - Godínez-Domínguez, Enrique (2001)
Three cruises, one in each of the main stream patterns in the area, were made on the central Mexican Pacific continental slope (May-June 1995, November 1995, and March 1996). Seven trawl sampling sites were defined per cruise, and in each site four bathymetric levels were sampled (20, 40, 60, and 80 m). During the warmest seasons, the highest abundance of Porichthys margaritatus was at 60 m. When the temperature of the bottom water was lower, in March 1996, the highest abundance of P. margaritatus moved towards 40 m. The depths with greatest abundance fluctuated between 18 and 21°C, indicating a narrow temperature preference range. A Gaussian model was used to explain the relation between abundance and temperature.